The effect of wearing soccer headgear on the head response in soccer heading - Tan, F. Y.; Hassan, M. H. A.; Johari, N. H.; Omar, M. N.; Hasanudin, I. (Universiti Malaysia Pahang, 2022)
Soccer is regarded as the most popular sport in the world, with millions of people actively involved in the game. Being a contact sport in nature, soccer players are susceptible to various kinds of injuries, such as lower extremities muscle injury. In addition to those familiar injuries that soccer players sustain during the game, traumatic brain injury is also a possibility. Head impacts in soccer could be a result of head-to-head impact with an opponent player, a head-to-elbow impact, an impact with the goal post, an impact with the ground, as well as an impact with the soccer ball, which occurs during a heading manoeuvre. Soccer allows the players to use their heads to hit the ball to pass it to a teammate or even perform heading to score a goal. Although soccer heading is perceived as less harmful as compared to head impacts with other hard objects, many studies have shown compelling evidence that this repetitive heading might harm the brain, thereby leading to traumatic brain injury. Protective headgears designed especially for soccer players have been commercially available in the market for some years. However, the effectiveness of these headgears in reducing the impact due to soccer heading has not been well studied. This paper investigates the effectiveness of two commercially available headgears, the Full90 and the ForceField headgear by means of a heading experiment. An anthropometric test device known as Hybrid III head and neck dummy instrumented with an inertial sensor that consists of a triaxial accelerometer and gyroscope installed at the centre of gravity of the head was used in the experiment. A soccer ball launching machine was used to propel the ball at several inbound velocities. Peak linear acceleration (PLA) and peak angular acceleration (PRA) were recorded, and the head injury criterion (HIC) and the rotational injury criterion (RIC) were calculated. It was found that both headgears failed to reduce the linear components of head acceleration but instead increased the HIC (13 – 66% increment) depending on the inbound ball velocity. With respect to the rotational component of head injury, the Full90 headgear was found to reduce the RIC up to 29%, but the ForceField failed to provide a significant reduction of RIC. Overall, both headgears were found to be ineffective in reducing linear and rotational components of head injury, which could be attributed to the headgear design. Improved headgear design and an improved padded foam are needed to protect soccer player’s brain while performing soccer heading.